Comparative Analysis of Soil Fertility in Sandy Soils along a Toposequence Transect in Sandai, West Kalimantan - Pulunggono, Heru Bagus; Pratiwi, Dea; Zulfajrin, Moh; Nurazizah, Lina Latifah; Chahyahusna, Affan; Iskandar (CELEBES Agricultural, 2024)
Addressing food crises and land degradation potential requires multisteps agricultural development, including soil fertility assessment. This study evaluates sandy soil fertility status along a toposequence transect in Sandai District, Ketapang Regency, West Kalimantan. Seven observation points (TP1, TP2, TP3, TK1, TK2, TK3, and TK4) were established, with soil samples collected from depths of 0-30 cm and 30-60 cm. Soil fertility assessment was conducted using three criteria: Five Major Soil Chemical Properties (FMSCP), Basic Cation Saturation Ratio (BCSR), and Sufficiency Level of Available Nutrients (SLAN). The FMSCP method exhibited low to very low fertility statuses, while the BCSR and SLAN methods revealed significant variations in soil fertility, ranging from deficient to excessive. Both the BCSR and SLAN methods demonstrated strong relationships with soil parent material and slope gradient, as evaluated through a multivariate approach. The BCSR method indicated deficient to balanced status at all profile points, whereas dominant balanced to excessive statuses were observed at all fertility points. The SLAN national criteria predominantly indicated deficient status for calcium (Ca), magnesium (Mg), and potassium (K), while the international criteria identified K deficiency only. This study served as forums to discuss fertility assessment in tropical soils. Also, recommends the potential for implementing the FMSCP criteria-based soil fertility assessment method for tropical Indonesian sandy soils and consider the involvement of balancing ratios in a more comprehensive soil fertility evaluation approach.